ПЕДАГОГІЧНІ УМОВИ ФОРМУВАННЯ ВІДПОВІДАЛЬНОГО СТАВЛЕННЯ ДО БАТЬКІВСТВА У СТУДЕНТІВ КЛАСИЧНОГО УНІВЕРСИТЕТУ В ПОЗААУДИТОРНІЙ ВИХОВНІЙ РОБОТІ - Смалько, Оксана (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті обґрунтовано педагогічні умови формування відповідального ставлення до батьківства у студентів класичного університету в позааудиторній виховній роботі. Відзначено, що ефективному формуванню відповідального ставлення до батьківства у студентів сприятиме реалізація в позааудиторній виховній роботі університету наступних педагогічних умов: формування у студентів позитивної мотивації та потреби у відповідальному батьківстві; оновлення (модифікація) змісту позааудиторної виховної роботи; використання інтерактивних форм і методів формування відповідального ставлення до батьківства. В статье обоснованно педагогические условия формирования ответственного отношения к родительству у студентов классического университета во внеаудиторной воспитательной работе. Отмечено, что эффективному формированию ответственного отношения к родительству у студентов будет способствовать реализация во внеаудиторной воспитательной работе университета следующих педагогических условий: формирование у студентов позитивной мотивации и потребности в ответственном родительстве; обновление (модификация) содержания внеаудиторной воспитательной работы; использование интерактивных форм и методов формирования ответственного отношения к родительству. Pedagogical terms of forming responsible attitude towards parenthood among students of classical university in extracurricular educational activities are determined. Formation of a responsible attitude to paternity the students considered as purposeful, controlled process and multifaceted impact on the consciousness, feelings and will of individual student to transform subjective personal values paternity super whole education in his totality resistant properties and qualities necessary future father / mother. It is noted that the effective formation of a responsible attitude to the students paternity facilitate implementation in extracurricular educational work of university teachers following conditions: formation of students’ positive motivation and the need for responsible paternity; modifying the contents of extracurricular educational work; interactive forms and methods of forming a responsible attitude to paternity; effective management of the process of forming a responsible attitude to paternity in university students.